Alternative Protocol Using Imipramine, Detomidine, and Oxytocin for Semen Collection in Stallion with Ejaculatory Dysfunction - Cavalero, Thaís M.S. [UNESP]; Segabinazzi, Lorenzo G.T.M. [UNESP]; Scheeren, Verônica F.C. [UNESP]; Canuto, Lucas E.F. [UNESP]; Gobato, Mariana L.M. [UNESP]; Papa, Frederico F. [UNESP] (Elsevier, 2020)
A 7-year-old Quarter Horse stallion was admitted at the hospital with a history of ejaculatory failure for 12 months. The stallion revealed no physical or psychological abnormalities, as well as, normal libido and erection. In addition, there were no abnormalities in accessory sex glands or the aorta artery detected by transrectal ultrasonography. Based on clinical findings, the stallion was diagnosed with an idiopathic ejaculatory dysfunction; therefore, alternative attempts of semen collection were performed. Thermal compress on the basis of the stallion's penis, semen collection on the ground, and imipramine hydrochloride treatment were performed unsuccessfully. However, a protocol consisted by the association of imipramine (3 mg/kg/v.o.), detomidine (0.02 mg/kg/i.v.), and oxytocin (20 U.I./i.v.) successfully produced ejaculation in this stallion. The semen obtained from ex copula ejaculation of the stallion was collected using a collector cup lined with a plastic bag, which was positioned over the prepuce of the stallion. Semen with good sperm quality (87% of total motility) was obtained using the proposed protocol. Semen was then processed for cryopreservation and post-thawed semen samples presented satisfactory sperm parameters. In conclusion, the association of imipramine, detomidine, and oxytocin can be considered for ex copula semen collection in stallions.
Keywords: Chemical ejaculation; Ejaculatory failure; Equine; Horse